Pengaruh Model Problem Based Learning Berorientasi Literasi Lingkungan Terhadap Keterampilan Berpikir Kritis Siswa Madrasah Ibtidaiyah - Binasdevi, Misbah (Indonesian Journal of Islamic Elementary Education, 2022)
This study aims to determine the effect of environmental literacy oriented problem-based learning on the critical thinking skills of Madrasah Ibtidaiyah students. The method used is quasi-experimental and the research design used is a non-equivalent control group design. The object of this research is the fifth-grade students of MI Darul Ulum, totaling 39 people consisting of 20 experimental class students and 19 control class students. The data collection instrument in this study was an observation and test instrument consisting of 5 questions about critical thinking. The data obtained were then analyzed using the t-test with the help of the SPSS application. Based on the data analysis,the results showed that there was a significant difference between the class that used the environmental literacy-oriented problem-based learning model and the class that continued to use the conventional learning model with an at-count value of 2.154 > 1.687 and also based on a significant value (2 tailed) 0.038 < 0.05 so that Ho is rejected. It can be concluded that there is an effect of the environmental literacy oriented problem-based learning model on the critical thinking skills of Madrasah Ibtidaiyah students.